Deteksi Dan Mitigasi Serangan Distributed Denial of Service Pada Software Defined Network - Pratiwi, Dheni Yulia Dinda; Adrian, Ronald (Maranatha University Press, 2024)
Software-Defined Networking (SDN) is an approach to network management that separates the control plane from the data plane of the network. In an SDN network, the control plane is centrally controlled by software called a